Marie-Sainton syndrome. Case reports - Reynaldo E. Delis Fernández; Raisa Escudero Alemán; Aída Pérez Alfonso (Acta Médica del Centro, 2011)
Marie-Sainton syndrome, also known as cleidocranial dysostosis, has a florid clinical picture dominated by changes in the clavicles and skull. Abnormalities in tooth eruption and dysmorphism are other distinctive features of this condition. Four female patients belonging to the same family and showing clinical and radiographic characteristics suggestive of cleidocranial dysplasia are reported here. These syndromes have a low incidence on medical practice, for this reason these patients are reported.